Implementation and Its Effect of Project Based Learning (PjBL) Model on Increasing Learning Output in Philology Course - Warni Warni; Rengki Afria (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to investigate the effect of implementing the Project Based Learning (PjBL) model on improving learning outputs in the Philology course. The research method used is a pseudo-experiment with a pre-test post-test control group design. The research subjects consisted of two groups of students, namely the experimental group that applied the Project Based Learning Model and the control group that used conventional learning methods. Data were collected through pre-test and post-test instruments, observations, and questionnaires. The results showed that the application of the Project Based Learning Model significantly improved student learning outputs in the Philology course. There is an increase in concept understanding, text analysis skills, and critical thinking skills of students who take part in learning with the PjBL approach. In addition, students' positive response to this learning model is also evident from the questionnaire results. This finding implies that the Project Based Learning Model can be used as an effective alternative in improving the quality of learning in Philology courses